Forensic intelligence framework. Part II: Study of the main generic building blocks and challenges through the examples of illicit drugs and false identity documents monitoring. (May 2015) - Baechler, Simon; Morelato, Marie; Ribaux, Olivier; Beavis, Alison; Tahtouh, Mark; Kirkbride, K. Paul; Esseiva, Pierre; Margot, Pierre; Roux, Claude
Highlights: Development of a transversal forensic intelligence process. Development of the comparison and evaluation processes in the forensic intelligence framework. Issues and challenges for an effective forensic intelligence function are addressed. Both qualitative and quantitative approaches are addressed. These formalisation efforts are pivotal to ensure the progress of the discipline. Abstract: The development of forensic intelligence relies on the expression of suitable models that better represent the contribution of forensic intelligence in relation to the criminal justice system, policing and security. Such models assist in comparing and evaluating methods and new technologies, provide transparency and foster the development of new applications. Interestingly, strong similarities between two separate projects focusing on specific forensic science areas were recently observed. These observations have led to the induction of a general model (Part I) that could guide the use of any forensic science case data in an intelligence perspective. The present article builds upon this general approach by focusing on decisional and organisational issues. The article investigates the comparison process and evaluation system that lay at the heart of the forensic intelligence framework, advocating scientific decision criteria and a structured but flexible and dynamic architecture. These building blocks are crucial and clearly lay within the expertise of forensic scientists. However, it is only part of the problem. Forensic intelligence includes other blocks with their respective interactions, decision points and tensions (e.g. regarding how to guide detection and how to integrate forensic information with other information). Formalising these blocks identifies many questions and potential answers. Addressing these questions is essential for the progress of the discipline. Such a process requires clarifying the role and place of the forensic scientist within the whole process and their relationship to other stakeholders.